1996
DOI: 10.1103/physrevlett.76.3947
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chaos, Irreversible Classical Dynamics, and Random Matrix Theory

Abstract: The Bohigas-Giannoni-Schmit conjecture stating that the statistical spectral properties of systems which are chaotic in their classical limit coincide with random matrix theory is proved. For this purpose a new semiclassical field theory for individual chaotic systems is constructed in the framework of the non-linear σ-model. The low lying modes are shown to be associated with the Perron-Frobenius spectrum of the underlying irreversible classical dynamics. It is shown that the existence of a gap in the Perron-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
202
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(206 citation statements)
references
References 17 publications
4
202
0
Order By: Relevance
“…On the other hand, it was shown in computer simulations [76] that there is a transition from chaotic [77,78] to localized eigenstates for the 2D Anderson problem [76], with an intermediate crossover region. We consider "rst the case when metal concentration p is equal to the percolation threshold p A "1/2 for the 2D bond percolation problem.…”
Section: Local Xeld Distribution In Percolation Composites With "!mentioning
confidence: 99%
“…On the other hand, it was shown in computer simulations [76] that there is a transition from chaotic [77,78] to localized eigenstates for the 2D Anderson problem [76], with an intermediate crossover region. We consider "rst the case when metal concentration p is equal to the percolation threshold p A "1/2 for the 2D bond percolation problem.…”
Section: Local Xeld Distribution In Percolation Composites With "!mentioning
confidence: 99%
“…Specifically, it was shown that in the semiclassical regime [4][5][6] the energy level density autocorrelation function of a chaotic system, evaluated at energy separations encompassing several mean level spacings, displays similar statistical properties as those arising from ensembles of random matrices [7]. Starting from the random matrix side, advances in proving the connection to the spectral fluctuations of chaotic systems were also achieved [8,9]. Although a full proof of Bohigas' conjecture is not yet available, its domain of validity is fairly established.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has become clear that RMT also describes single-particle quantum dynamics which is chaotic in the classical limit [2,3]. Examples are non-interacting electrons in small disordered metallic grains [4], and in ballistic quantum dots [5]. Real systems, however, contain a large number of interacting particles, and a question which naturally arises is how does chaos in a single-particle description manifest itself in the properties of the true many-body problem?…”
mentioning
confidence: 99%